A Reactive Molecular Dynamics Simulation Study of the Mechanical Response of Amorphous Sulfur–Graphitic Carbon Composite Cathodes. Issue 13 (27th August 2019) - Verners, O.; Simone, A.
Abstract : The study explores the use of a composite, graphitic carbon (GC) – sulfur (S) based cathode in laminated structural batteries. Specifically, failure by delamination is studied with regards to the applicability of a double-walled tube architecture obtained by coating the inner surfaces of hollow carbon nanofibers with sulfur. Differences between the material responses of various Li X S ( X ∈ (0, 2)) compounds under bulk-like and interface confined conditions are discussed in terms of the shear response of physically and chemically bonded interfaces, formed with non-functionalized and H/OH/O-functionalized GC surfaces. The study indicates that only a chemically bonded interface with non-functionalized GC yields bulk-compatible mechanical behavior, with the exception of concentrations of X ∈ (0.8, 1.1). To strengthen the interface at low Li concentrations, at which a pronounced inhomogeneity in mass density in terms of interface debonding occurs, a modified transition layer was tested. The results indicate a distinct improvement in terms of homogeneity of mass density and plastic strain localization. The effect of delithiation at high rates on the interface structural stability is investigated at different concentrations of Li in structures of initially uniform Li distribution. According to the results, delamination failure is likely to occur.